Beyond Compliance: Uncovering Organizational Aspects of Award-Winning Environmental Performance (Journal of Governance and Development (JGD), 2014)
Effective design and management of environmental regulations requires an understanding of the factors that lead organizations to comply with the environmental rules they face. The regulatory and organizational behavior literatures suggest that ï¬ rmsâ€™ motivation for rule compliance emerges from the instrumental, social, or norm-based consequences of complying that the organization perceives. In addition to motives, operational aspects of compliance including organizationsâ€™ capacities, knowledge, and technological assets, should also be considered. Understanding the environmental compliance behavior of top performing ï¬ rms allows regulators to strategically plan their compliance interventions, and also showcases best practices for other regulated ï¬ rms to emulate. Interviews were conducted with facility managers at environmental award-winning facilities in the U.S. state of South Carolina to identify motivational and operational aspects of compliance among top-performers. The ï¬ ndings suggest these organizationsâ€™ relations with their communities, customers, and production chains have the greatest inï¬‚ uence on their environmental performance. Social pressures for regulatory compliance similar to these also appear in the Southeast Asian context, where â€œenforcement gapsâ€ are more prevalent. Irrespective of place, environmentally excellent ï¬ rms set the pace for new regulatory regimes, and can assist both regulators and poorer performers alike.